Herd Behaviour and Market Efficiency: Evidence from the Iberian Stock Exchanges - CURTO, José Dias; FALCÃO, Pedro Fontes; BRAGA, André Almeida (Journal of Advanced Studies in Finance; Vol 8 No 2 (2017): JASF Volume VIII Issue 2(16) Winter 2017, 2018)
The present paper examines the extent to which herd behaviour is prevalent in the Iberian stock markets using constant and time-varying coefficient estimation. An important finding is that the results obtained from using the two different methodologies for analyzing the Iberian markets lead to different conclusions, suggesting that estimates are not independent of the methodology used. Using constant coefficient methodologies no evidence of herding is found in the Spanish market suggesting a generally efficient market, however regarding the Portuguese market we find evidence of herd behaviour. On the other hand, by employing the Kalman filter, a methodology scarcely used in the study of the herding phenomenon, we find that herd behaviour presents time-varying dynamics in both Iberian markets. Additionally, the issue of a potential contagion across these two highly integrated economies is also addressed and the evidence suggests a strong spillover effect. The findings, particularly those regarding the time-varying dynamics of herding, highlight the necessity of further research given the impact of herding on market stability and particularly on portfolio risk diversification.